1997
DOI: 10.1016/s0014-5793(97)01083-1
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone suppresses apoptosis in a human gastric cancer cell line through modulation of bcl‐x gene expression

Abstract: Treatment of human gastric cancer TMK-1 cells with transcription and translation inhibitors rapidly triggered cell apoptosis. Along with cell apoptosis, the Bcl-xs level was markedly upregulated suggesting a crucial role of this protein in promoting the apoptotic process. In the presence of dexamethasone, however, cell apoptosis was greatly attenuated as demonstrated by DNA histogram shift and DNA fragmentation. Studies using the glucocorticoid receptor antagonist Rl 486 indicated that attenuation of apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 20 publications
2
36
2
Order By: Relevance
“…The enhanced bcl-xL mRNA and protein levels in rat hepatocytes appear to represent a part of the mechanism underlying the protective effect of DEX. Chang et al, 51 showed that the expression of the bcl-x gene in TMK-1 cells is regulated by DEX at both posttranscriptional and translational levels. Our results indicate that transcriptional mechanisms are important.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced bcl-xL mRNA and protein levels in rat hepatocytes appear to represent a part of the mechanism underlying the protective effect of DEX. Chang et al, 51 showed that the expression of the bcl-x gene in TMK-1 cells is regulated by DEX at both posttranscriptional and translational levels. Our results indicate that transcriptional mechanisms are important.…”
Section: Discussionmentioning
confidence: 99%
“…To verify that both splice variants were being affected over the time periods presented, we used a ribonuclease protection assay that was highly quantitative. Using this assay, Bcl-x(L) was shown to decrease with ceramide treatment (following the published half-life of ϳ14 h for Bcl-x(L) mRNA) as well as caspase 9b while caspase 9 and Bcl-x(s) were both demonstrated to in- crease significantly (67,68). Since both splice variants are affected in response to ceramide, transcriptional effects are an unlikely mechanism of action as both splice variants would be affected in the same direction.…”
Section: Exogenous Ceramide Regulates the Alternative Splicing Ofmentioning
confidence: 94%
“…Glucocorticoids were found to enhance the cytotoxicity of cisplatin via suppression of NF-κB activation in the GR-rich human cervical carcinoma cell line SiHa [88,89]. On the other hand, other studies have shown that glucocorticoids decrease the chemosensitivity in non-hematological solid tumors cells through a variety of mechanisms, which include the modulation of bcl-x gene expression, and the up-regulation of p21 Cip1 and mitogenactivated protein kinase phosphatase-1 (MKP-1) [22,97,159].…”
Section: Pre-clinical and Clinical Trials Of Nf-κb Inhibitorsmentioning
confidence: 99%